Effectiveness of a reading intervention program for ASD with technologies: a personalized approach, based on the phonetic method and the RAN - Muñoz López, Juana; Lozano López, Nieves; Garrido, Dunia (Revista de Investigación en Logopedia, 2026)
In recent years, reading intervention and teaching programs for children with autism spectrum disorder (ASD) have been developed based on the phonetic method. These programs are applied with technologies that allow personalized interventions. The objective of this study is to analyze the effectiveness of an intensive and personalized intervention using the INVENTAPALABRAS (Muñoz et al., 2025) software to address reading difficulties in a child with ASD (support level 1), focusing on the National Reading Panel (NRP, 2000) components and rapid automatic naming (RAN) training. The intervention lasted 35 hours and was divided into three phases: (a) pre-test evaluation; (b) training in the five NRP and RAN elements: colors, objects, and numbers; and (c) post-test evaluation. The results showed improvements in phonological awareness, with an increase in the overall score from 4,01 to 5,94, a reduction in the time spent on RAN tasks, and improvements in accuracy, reading speed and comprehension. In conclusion, this study demonstrates and supports that a structured, individualized, computer-based intervention addressing deficits in phonological processing and RAN could effectively improve reading difficulties in people with ASD.